Politeness strategies in English and Vietnamese on social media - Hoàng, Kim Thành (Trường Đại học Đà Lạt, 2025)
The purpose of this study is to look into the details of how commenters consider and use politeness strategies in English and Vietnamese on social media, with an emphasis on reducing or eliminating cases of cyberbullying